Servos das leis fatais: a ironia e o trágico em Os Maias de Eça de Queirós - Salles, Juliana Rodrigues (2016)
Eça de Queiroz is one the writers that better managed to perform a reliable portrait of the society he was inserted: the Portugal of the Nineteenth century’s second half. A good deal of his work represented the decaying of his nation and the more predominant social addictions. The present dissertation makes, in the first place, a synthesis of the author’s projects, with the predominant themes and plots, since the Farpas until the Cenas Portuguesas. In a second moment, it’s analyzed the expedient of irony, ably used by the writer to treat with sarcasm, satire and pessimism the tragic themes of his principal novels. The central objective of this text is finding out in Os Maias (1888) the signals of the coming tragedy through the analysis of extracted excerpts from the narrative. To do so, the last chapter deal initially with the tragedy theory, that gives support to the reading of the chosen excerpts for analysis, these excerpts demonstrate the evidence left by the author that all the action in the novel moves gradually to a tragic upshot. Through the presence of irony and tragedy, our work reiterates that the main question of Os Maias goes far beyond of a love story with a tragic ending, it’s a work that includes more embracing and complex questions than the incest, but that Eça’s writing reveals only to the more attentive eyes.